SPEED UP YOUR PYTHON WITH RUST optimize python performance by creating python pip modules in rust. - FLITTON, MAXWELL (PACKT PUBLISHING LIMITED, 2022)
Discover how to inject your code with highly performant Rust features to develop fast and memory-safe applications Key Features Learn to implement Rust in a Python system without altering the entire system Write safe and efficient Rust code as a Python developer by understanding the essential features of Rust Build Python extensions in Rust by using Python NumPy modules in your Rust code Book Description Python has made software development easier, but it falls short in several areas including memory management that lead to poor performance and security. Rust, on the other hand, provides memory safety without using a garbage collector, which means that with its low memory footprint, you can build high-performant and secure apps relatively easily. However, rewriting everything in Rust can be expensive and risky as there might not be package support in Rust for the problem being solved. This is where Python bindings and pip come in. This book will help you, as a Python developer, to start using Rust in your Python projects without having to manage a separate Rust server or application. Seeing as you'll already understand concepts like functions and loops, this book covers the quirks of Rust such as memory management to code Rust in a productive and structured manner. You'll explore the PyO3 crate to fuse Rust code with Python, learn how to package your fused Rust code in a pip package, and then deploy a Python Flask application in Docker that uses a private Rust pip module. Finally, you'll get to grips with advanced Rust binding topics such as inspecting Python objects and modules in Rust. By the end of this Rust book, you'll be able to develop safe and high-performant applications with better concurrency support. What you will learn Explore the quirks of the Rust programming language that a Python developer needs to understand to code in Rust Understand the trade-offs for multiprocessing and thread safety to write concurrent code Build and manage a software project with cargo and crates Fuse Rust code with Python so that Python can import and run Rust code Deploy a Python Flask application in Docker that utilizes a private Rust pip module Inspect and create your own Python objects in Rust Who this book is for This book is for Python developers who want to speed up their Python code with Rust and implement Rust in a Python system without altering the entire system. You'll be able to learn about all topics relating to Rust programming. Basic knowledge of Python is required to get the most out of this book.